Didactic Principles Aimed at the Development of Electronic Publications (Eurasian Research Bulletin, 2022)
This article presents didactic principles focused on the development of electronic publications. In addition, theoretical analyzes are presented on the development of students ' preparations for graphically visualizing using computer technology.